Implementasi Permainan Lempar Dan Tangkap Bola Dalam Meningkatkan Kemampuan Motorik Kasar Aud Di Paud Kober Assyamsi Kabupaten Garut - Aisyah, Siti (CV. ITTC INDONESIA, 2024)
Implementation of the game of throwing and catching the ball in improving the gross motor skills of early childhood in Kober Assyamsi preschool, Garut district (4-5 year age group) (2024). Thesis. Bekasi Panca Sakti University Bekasi. This research aims to determine the improvement of gross motor skills in children aged 4-5 years through throwing and catching ball games at PAUD Kober Assyamsi Garut. Gross motor skills refer to exercises that involve the large muscles of the body. The activity of throwing and catching a ball can help children's physical development, such as endurance and muscle strength. This research is classroom action research (PTK). Children aged 4-5 years (group A) totaling 15 children consisting of 8 boys and 7 girls were the subjects of this research. This research was carried out at PAUD Kober Assyamsi, Garut Regency. The data collection technique used by researchers is complete participant observation, which means that in collecting data, researchers are involved in learning. By using learning through interesting, interactive, and memorable games of throwing and catching balls, which are expected to build creativity, wise adaptation, and the support of parents and educators, children can experience the deep joy of learning while improving their gross motor skills. The initial ability of pre-cycle students was 34.5% (BB), Cycle I 49.7% (MB), and Cycle II 78.7% (BSH).